An Analysis Types of Directive Speech Act Used By The Main Character Utterances In “Captain Lightyear” Movie: Pragmatic Approach - Hakim, Muhammad Arsyad; Mubarak, Zia Hisni (LPPM Universitas Putera Batam, 2024)
This applied a pragmatic study to obtain the types of directive speech acts in the movie “Captain Light year” directed by Angus Maclane. The purpose of this study was to analyze the types of directive speech act contained in the movie. Then, the speech was analyzed and classified by applying the theory of Searle and Vanderveken (1985) to the data source. The data source for this research was the directive speech act uttered by the main characters in the movie “Captain Lightyear”. To get the desired research results, the researchers used descriptive qualitative method. The Data collection technique researcher used observation technique. Before the researcher conducts data collection, the researcher must take the following steps: The researcher will watch the Captain Lightyear movie, after watching the movie, the researcher will identify and record the data to be analyzed, and then the researcher will group the data from the type of directive speech acts found in the captain lightyear movie. The data from this study was analyzed using pragmatic method. The researcher found utterances of directive speech acts in the speech of the main characters. The researcher found 5 types of directive speech acts and the result researcher found 15 data, including (8) asking, (3) ordering, (1) advising, (2) request, and (1) begging. The researcher has found a type of directive speech act in the form of asking questions used by the main character in the movie Captain Lightyear. The reason is because the speaker has the intention to get information and wants to get an answer.